(3TQM GHf GdfajSs - (3GdcQeGfj, HQgGf GdOjf, fajS Hf YhV Hf Mcje, J (B841(3g`s ((3eMeO YRjR Hf ebUhO Ydjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3CeG HYO ajbhd GdYHO GdabjQ(B... (3Efj bO cfJ ef Cgd HjJ eTghQjf HgPg GdUfGYI RGHJdjJ aj YfahGf GdUHi hQjYGf GdTHGH HeRGhdI GdYdGL(B...s
(3BNQgG (B:s
(3hMOK aj GdeaUd YfO GdYhO ZhQ HeG jONd ajg GdCUHZ dYXeg(B... (3hYdGLg QO GdYXe GdeSJQNj Edi OGNd eSJbQg GdPj RGd Yfg hJVejOg HGdCVeOI(B... (3aEfgG jTO GdYVh hjfTa GdQWhHGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B8(3, U(B44s
(3GdCYdGe(B: (3L(B8(3, U(B44s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdWHs